2009
DOI: 10.1038/onc.2009.422
|View full text |Cite
|
Sign up to set email alerts
|

Calpain regulates sensitivity to trastuzumab and survival in HER2-positive breast cancer

Abstract: Resistance to anti-HER2 (human epithelial growth factor receptor 2) trastuzumab therapy occurs commonly in HER2-positive breast cancer and involves overactivation of HER2 and/or AKT1. Using the model of trastuzumabsensitive or trastuzumab-resistant HER2-positive cells with wild-type PTEN, negative regulator of AKT1, we explore the involvement of cysteine protease calpain in mechanisms of trastuzumab resistance. Overexpression of calpain1 or activation of endogenous calpain during adhesion or trastuzumab treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…Following this assumption and because the molecular weight of proteins varies with cell-specific posttranslational modifications, samples from breast tumors analyzed by Western blot were classified as p95HER2-positive if immunoreactivity was detected in the 90 to 115 kDa region. Additional fragments arise through proteolytic cleavage of the intracellular domain of HER2 by caspases (33) and calpains (34). However, the molecular size of these fragments is <50 kDa (33,34), and therefore, they have not been considered within the p95HER2 group of fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this assumption and because the molecular weight of proteins varies with cell-specific posttranslational modifications, samples from breast tumors analyzed by Western blot were classified as p95HER2-positive if immunoreactivity was detected in the 90 to 115 kDa region. Additional fragments arise through proteolytic cleavage of the intracellular domain of HER2 by caspases (33) and calpains (34). However, the molecular size of these fragments is <50 kDa (33,34), and therefore, they have not been considered within the p95HER2 group of fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Additional fragments arise through proteolytic cleavage of the intracellular domain of HER2 by caspases (33) and calpains (34). However, the molecular size of these fragments is <50 kDa (33,34), and therefore, they have not been considered within the p95HER2 group of fragments. In contrast to the original hypothesis, we have shown recently that, in addition to proteolytic processing, alternative initiation of translation from different methionine codons can generate HER2 CTFs (21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent report showed that calpain inhibition could resensitize herceptin-resistant variants of these HER2 ϩ cells (36). Calpain knock-out in the chondrocyte lineage in mice has also been associated with decreased proliferation correlating with increased p27…”
Section: Figure 6 Calpain 2 Regulates In Vivo P27mentioning
confidence: 99%
“…data]. In vitro studies have shown that calpain-4 enhances survival following trastuzumab treatment; however, suppression of calpain-1 activity has also been linked with trastuzumab response in HER2-positive breast cancer cell lines [103,104]. How the calpain system may regulate the response to trastuzumab is unclear, but evidence indicates that calpain- mediated cleavage of IκBα is involved in HER2-induced NF-κB activation and, inversely, that HER2 overexpression blocks calpain activity by up-regulating calpastatin [48,105].…”
Section: The Calpain System and Response To Breast Cancer Treatmentsmentioning
confidence: 99%